Relevance of organizational justice on the turnover intentions of millennials in the oil and gas industry of Malaysia - Kong, Kok Loong (2021)
Employee turnover is a recurring challenge that all organizations face in today’s highly competitive environment since employees are an organization’s most valuable assets and when they resign, there will be substantial financial costs incurred. With millennials found to form the largest share of the workforce from 2020 to 2030 in many countries including the UK, U.S., Australia, Brazil and Malaysia (Cush & Wakefield, 2020) and are leaving organizations at a higher rate than other generations (Simmons, 2016); the challenges associated with the turnover of millennial have become emphasized especially for the Oil and Gas (O&G) industry. This especially when the industry had already been grappling with multiple human resource related challenges like employee retention, inadequate pipeline of skilled employees available to replace experienced workers who retire and the significant turnover of specialized employees. Having a good understanding of millennials’ perceptions of organizational justice who are working in the O&G industry and how they go towards affecting the millennials’ turnover intentions have become of paramount importance. This study thus sets out to qualitatively evaluate all under one umbrella the views of millennials working in the O&G industry of Malaysia on what their perceptions of organizational justice are and how these perceptions affect their turnover intentions. Organization justice will be looked at from the dimensions of distributive, procedural and interactional justice. Primary data were collected through semi-structured interviews with 10 millennial employees from companies operating within in the O&G industry of Malaysia. Based on the results that were collected and analyzed, it was found that millennial employees in the O&G industry of Malaysia have low perceptions of distributive justice, moderate perceptions of procedural justice and high perceptions of interactional justice. The results had also provided evidence to support the negative relationship between the three dimensions of organizational justice and turnover intentions; and that both distributive and interactional justice were found to be stronger predictors of turnover intentions than procedural justice. Based on these findings, an employee retention framework that involves distributive, procedural and interactional justice retention strategies was conceptualized and recommended to HR practitioners within the O&G industry for use to optimize the retention of their millennial employees and it is hoped that in doing so, timely interventions in the millennial employees’ withdrawal process to be made before it is becomes too late.